„The Text Was Considered Miraculous”. Magic Words in Pasternak’s „Doctor Zhivago” - Stanton, Rebecca Jane (Poznańskie Studia Slawistyczne, 2013)
In Doctor Zhivago, Pasternak brings scientific and political discourses into dialogue with magical ones. In an emblematic episode, two soldiers from opposing sides each wear a protective amulet containing the „miraculous” text of the 90th Psalm. One dies; one survivesWhile this discrepancy is easily traced to scientific and socioeconomic causes, the episode isdesigned to foreground the least rational explanation: that done right, magic actually worksEmbodying Pasternak’s interest in the interrelationships among science, politics, poetry, andmagic, the textual amulet is especially significant because it represents a magical power that is reserved for words. This article finds that Pasternak’s novel contains numerous examples of such efficacious „magical” texts – from the Gospels to peasant songs, from political slogans to Zhivago’s poems – and argues that reading Doctor Zhivago by the light of these„magic words” yields insights into the aesthetics and design of the novel.